2019
DOI: 10.1097/ipc.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Candidiasis in an Immunocompetent Woman

Abstract: Pylephlebitis, or portal vein thrombus infection, is a rare condition that is often missed owing to the nonspecific nature of its signs and symptoms and an underappreciation of the clinical entity. Causative microbes are typically bacteria, although cases of candidal pylephlebitis have been described. Given the invasive technique required to culture the portal vein, antimicrobial selection typically relies on the assumption that the microbes isolated in blood culture are the same as those infecting the portal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Gottlieb et al reported an immunocompetent woman who developed Candidal hepatic abscesses as a result of pylephlebitis. However, the causative species was Candida dubliniensis in this case [ 9 ]. Menachery et al and Hasan et al both reported a solitary C. albicans liver abscess in their patients [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gottlieb et al reported an immunocompetent woman who developed Candidal hepatic abscesses as a result of pylephlebitis. However, the causative species was Candida dubliniensis in this case [ 9 ]. Menachery et al and Hasan et al both reported a solitary C. albicans liver abscess in their patients [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A contrast-enhanced CT scan is the most sensitive investigation, typically depicting multiple, round, hypoattenuating lesions with a central enhancement. A percutaneous liver biopsy can help the definitive diagnosis of Candida in almost three-quarters of the patients if performed [ 9 ]. A diagnostic laparoscopy revealing white lesions on the liver surface can also aid in diagnosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%